Efficient hydrogen evolution from water using CdTe photocathodes under simulated sunlight. Issue 25 (13th June 2017) - Su, Jin; Minegishi, Tsutomu; Domen, Kazunari
Abstract : CdTe-based photocathodes have shown an extremely high incident photon-to-current conversion efficiency (IPCEs) of >95% at 560–660 nm with an applied potential of 0 VRHE . Abstract : CdTe-based photocathodes have shown an extremely high incident photon-to-current conversion efficiency (IPCEs) of >95% at 560–660 nm with an applied potential of 0 VRHE . In the present study, the effects of a back contact and annealing in the presence of CdCl2 on the PEC properties of CdTe-based photocathodes were investigated. Structural characterization demonstrated that the grain structure of CdTe thin films deposited on Cu and/or Au-coated fluorine-doped tin oxide (FTO) substrates was significantly affected. These structural differences were attributed to Cu diffusion during the CdTe deposition process and to the characteristics of the interfaces between the CdTe layer and the substrate. Further investigations also determined that the CdCl2 treatment eliminated impurities in the CdTe films. PEC measurements revealed that Pt- and CdS-modified CdTe photocathodes deposited on Cu and Au-coated FTO substrates exhibited three times higher half-cell solar-to-hydrogen conversion efficiency (HC-STH) values than a reported photocathode prepared on an FTO substrate. This enhancement resulted from the improved structural properties and the facilitated charge transfer between the CdTe and the substrate through the thinning of the Schottky barrier and the relatively large work function of Au. CdCl2 treatment further improved the extent of hydrogen evolution from water when using CdTe-based photocathodes; a photocathode treated with CdCl2 produced a relatively large cathodic photocurrent of −22 mA cm −2 at 0 VRHE under simulated sunlight. In addition, the HC-STH for this device was 3.7% at 0.3 VRHE . The photocathodes generated relatively stable photocurrents over 70 min and evolved hydrogen with a faradaic efficiency of approximately 100%.